Analisis Loneliness (Perasaan Kesepian) Pada Lansia Di Unit Pelaksana Teknis Pelayanan Sosial Tresna Werdha Jember Kecamatan Puger - Fita Yatul Mauviroh; Surayadi Suryadi (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
Loneliness is a negative emotional state experienced by individuals due to the lack of satisfying social interactions. In response to this issue, the government has established nursing homes that aim to address social problems, particularly psychological challenges among the elderly, such as feelings of loneliness. This study aims to explore the underlying factors contributing to loneliness among older adults residing in a nursing home and to examine the institutional efforts and facilities provided to mitigate such emotional experiences. A qualitative research approach with a descriptive design was employed in this study. The participants consisted of three elderly residents and one staff member from the nursing home, selected through purposive sampling. Data collection methods included observation, semi-structured interviews, and documentation. The data were analyzed using the processes of data reduction, data presentation, and conclusion drawing. The results indicate that most elderly residents in the nursing home experience loneliness. Key contributing factors include the loss of a spouse, limited social interaction, feelings of abandonment, and a perceived lack of purpose. The psychological impacts of loneliness identified in this study are categorized into emotional loneliness and social loneliness.